2022
DOI: 10.3390/jcm11041064
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration: New Insights in Diagnosis, Treatment, and Prevention

Abstract: Age-related macular degeneration (AMD) is an aging-related ocular disease that can be responsible for severe loss of visual acuity and loss of autonomy in patients [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…With the increasing elderly population, visual impairment is to be anticipated 18 . Currently, cataract surgery remains as the leading eye surgeries specifically in the aging population 6,[19][20][21] . In several research, cataract surgery increased the risk of AMD progression, such as the studies by Gan et al ( 2020) and Ho et al ( 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increasing elderly population, visual impairment is to be anticipated 18 . Currently, cataract surgery remains as the leading eye surgeries specifically in the aging population 6,[19][20][21] . In several research, cataract surgery increased the risk of AMD progression, such as the studies by Gan et al ( 2020) and Ho et al ( 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The longer the time is, the further Although both of the research studied about the possible association between cataract surgery and AMD, other studies found that there are no significant correlation and risk 22,23 . A meta-analysis of AMD progression and cataract surgery has been done previously and state similarly with the follow-up of 6-10 months 6,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation